Analyzing the risk factors for a diminished oocyte retrieval rate under controlled ovarian stimulation. (26th December 2016) - Nakamura, Mayumi; Yamashita, Yoshiki; Hayashi, Atsushi; Saito, Natsuho; Yu, Masae; Hayashi, Masami; Terai, Yoshito; Ohmichi, Masahide
Abstract: Aim: To investigate which risk factors contribute to a lower oocyte retrieval ratio in women who are receiving controlled ovarian hyperstimulation. Methods: The authors retrospectively analyzed 329 in vitro fertilization (IVF) cycles under controlled ovarian hyperstimulation by using a gonadotropin‐releasing hormone antagonist or agonist at Osaka Medical College, Japan. The patients were classified into five groups: advanced age, male infertility, severe endometriosis, tubal infertility, and unexplained infertility. The primary outcomes were the patients' age, oocyte retrieval ratio, serum basal follicle‐stimulating hormone, total dose of gonadotropin, and the clinical outcome. A secondary outcome was the stepwise multivariate logistic regression analysis to assess the factors associated with the failure of oocyte retrieval. Results: The oocyte retrieval ratio declined significantly with the patient's age. The ratio of endometriosis in unsuccessful cases was significantly higher than that in successful cycles. Advanced age and endometriosis were the factors that were significantly associated with a lowered oocyte retrieval rate. Conclusion: Advanced age and endometriosis are high‐risk factors that contribute to oocyte retrieval failure in infertile patients who are receiving IVF treatment.